2017
DOI: 10.1007/s11523-017-0522-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Simple Scoring System to Predict Sorafenib Effectiveness in Patients with Hepatocellular Carcinoma

Abstract: We have validated a useful scoring system to predict outcomes in sorafenib-treated HCC patients. This score is easy to calculate and suitable for implementation in daily clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…The median OS of the present analysis was 11.4 months. Similar survival data have been obtained by Di Costanzo et al in an Italian cohort comprising 279 patients with sorafenib-treated advanced HCC with a median OS of 10.8 months [ 23 ] and in another study with 288 HCC patients with a median OS of 13.6 months [ 14 ]. In a recently published cohort from our department, including 1119 patients with HCC treated in an 11-year period, the median survival of all patients was 15.3 months [ 24 ].…”
Section: Discussionsupporting
confidence: 81%
“…The median OS of the present analysis was 11.4 months. Similar survival data have been obtained by Di Costanzo et al in an Italian cohort comprising 279 patients with sorafenib-treated advanced HCC with a median OS of 10.8 months [ 23 ] and in another study with 288 HCC patients with a median OS of 13.6 months [ 14 ]. In a recently published cohort from our department, including 1119 patients with HCC treated in an 11-year period, the median survival of all patients was 15.3 months [ 24 ].…”
Section: Discussionsupporting
confidence: 81%
“…This aetiological non-homogeneity can be attributed to the expected greater frequency of diabetes in patients with metabolic liver disease. In addition, we also reported an increased toxicity in patients treated with insulin, probably related to the most significant response in patients with increased sorafenib toxicity [12,18].…”
Section: Discussionmentioning
confidence: 66%
“…The study reported a strong correlation between this classification and disease progression at 3 mo (41.9%, 25.9% and 12.7% of patients in groups 0, 1 and 2, respectively; P = 0.014). These data were subsequently confirmed in the validation cohort[ 24 ]. A recent meta-analysis by Abdel-Rahman et al[ 25 ] revealed an association between specific side-effects (hypertension, HFSR and diarrhea) and patient outcome (HR = 0.38; 95%CI: 0.30-0.48; P < 0.00001).…”
Section: Clinical Parametersmentioning
confidence: 74%